The structure of the nitrosyl [RuCl3(NO)(AsPh3)2] complex - Souza, D. H F [UNESP]; Oliva, G.; Teixeira, A.; Batista, A. A. (Elsevier, 1995)
The structure of the title compound, [RuCl3(NO)(AsPh3)2], has been determined by X-ray diffraction. The ruthenium atom is octahedrally coordinated with the arsine ligands in the trans configuration. The ν(NO) was found at 1869 cm-1 in the IR spectrum, which is consistent with the linearity of the RuNO bond angle. © 1995.